3D neutronic/thermal-hydraulic nuclear reactor core calculation (NRCC) code development for PWRs. (December 2020) - Aghili Nasr, Mahdi; Zangian, Mahdi
Abstract: For some nuclear problems, such as fuel loading pattern optimization (LPO), a computing code is required that in addition to the ability in multi-physics calculations, has a high computational speed. In this paper, an efficient coupling method is proposed for the neutronic and thermal-hydraulic (NTH) simulation of a pressurized water reactor (PWR) during the fuel cycle and the Nuclear Reactor Core Calculations (NRCC) code is developed to verify it. This code has an acceptable capacity for LPO problems owing to the use of simple methods of average current nodal expansion in neutronic calculations, two-phase single heated channel in thermal-hydraulic calculations, and a method for cross sections interpolation of library files. In order to test the models proposed, the results of NRCC code modeling for the core of the BEZNAU NOK reactor were verified against PARCS 2.7 and COBRA-EN using the code-by-code method. The numerical results show that the methods used for high-speed multi-physical calculations have good accuracy. Graphical abstract: Image 1 Highlights: The NRCC code has been developed for static core calculations of PWRs. The 3D thermal-neutronic internal coupling is performed during the fuel cycle. The NRCC code neutronic calculations are performed using average current nodal expansion method. The NRCC code thermal-hydraulic calculations are performed using homogeneous two-phase single heated channel method. PARCS2.7 and COBRA-EN codes have been used for NRCC code by code verification.